Lipid accumulation by NaCl induction at different growth stages and concentrations in photoautotrophic two-step cultivation of Monoraphidium dybowskii LB50. (July 2015) - Yang, Haijian; He, Qiaoning; Hu, Chunxiang
Highlights: Lipid production in LEGP is the highest with 20 g L −1 NaCl induction. With NaCl induction, lipid content and quality were improved in all growth phases. Sugar or protein competed for carbon with lipid under different NaCl concentrations. ADU decreased, reducing the membrane fluidity when NaCl induction was applied. The improved lipid quality was mainly for increasing CN and a slight decline of CFPP. Abstract: NaCl induction in photoautotrophic two-step cultivation is very promising, but time node and concentration are critical to the entire production. In this study Monoraphidium dybowskii LB50 was subjected to different NaCl concentrations at different growth phases. Results showed that during the initial phase (IP), fixed carbon was used for sugar and lipid under 5 g L −1 NaCl induction, as well as for protein under 10 g L −1 NaCl induction. At late-exponential growth phase (LEGP), the highest lipid productivity was obtained at 20 g L −1 NaCl. At stationary phase (SP) the highest lipid productivity was also under 20 g L −1 NaCl but lower than that of LEGP. In summary, lipid content and quality were improved at all growth phases under NaCl induction. Therefore, cultivation scale can be sued to determine the time node and dosage of the inducer, thereby realizing the economic efficiency of the fundamental guarantee in photoautotrophic two-step cultivation.